2016
DOI: 10.1016/j.jnucmat.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of atmospheric gases by bulk lithium metal

Abstract: Lithium conditioning of plasma facing components has enhanced the performance of several fusion devices. Elemental lithium will react with air during maintenance activities and with residual gases (H 2 O, CO, CO 2 ) in the vacuum vessel during operations. We have used a mass balance (microgram sensitivity) to measure the mass gain of lithium samples during exposure of a ~ 1 cm 2 surface to ambient and dry synthetic air. For ambient air, we found an initial mass gain of several mg/h declining to less than 1 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…A study on sorption of atmospheric gases by bulk Li metal 24 measured mass gain rates in room temperature, artificial dry air of roughly 0.2 mg cm −2 h −1 .…”
Section: B Mass Measurement Errorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study on sorption of atmospheric gases by bulk Li metal 24 measured mass gain rates in room temperature, artificial dry air of roughly 0.2 mg cm −2 h −1 .…”
Section: B Mass Measurement Errorsmentioning
confidence: 99%
“…The boxes have an internal surface area of 150 cm 2 . If 6 min elapses during transfer from the vacuum chamber to the glovebox and the gas is as dry as the artificial dry air (estimated at 3.3% relative humidity 24 ), then the mass gain per box is estimated at 3 mg. This is < 1% of the predicted Li efflux from the third box (Table I).…”
Section: B Mass Measurement Errorsmentioning
confidence: 99%
“…Zavadil and Armstrong have made significant contribution to explore the chemistry of small molecules on lithium surface [49,50] . The work carried out to determine the rate of passivation of lithium metal with the exposure of environmental gases clearly advocates the high susceptibility of lithium towards these gases [51] . H 2 S reaction on the surface of lithium was studied long ago and characterized employing X‐ray photoelectron spectroscopy (XPS) [52] .…”
Section: Introductionmentioning
confidence: 99%
“…[49,50] The work carried out to determine the rate of passivation of lithium metal with the exposure of environmental gases clearly advocates the high susceptibility of lithium towards these gases. [51] H 2 S reaction on the surface of lithium was studied long ago and characterized employing X-ray photoelectron spectroscopy (XPS). [52] Results suggest that H 2 S undergoes SÀ H dissociation leading to the formation of sulphide layer of relatively small thickness, and spectroscopic data denies the presence of sulfhydryl (LiSH) on the Li surface.…”
Section: Introductionmentioning
confidence: 99%
“…Pilling and Bedworth found that it depends on the relative molar volume of a metal and the corresponding metal oxide if the metal oxide can form a covering and protective layer on the metal. 6,7 To classify different metal oxides, the Pilling-Bedworth ratio is calculated as follows: For a ratio smaller than one, the oxide film is unprotective, as it will be porous and/or cracked. Consequently, the oxidation reaction is not self-limiting and the thickness of the oxide film will increase steadily.…”
Section: Si 9: Pilling-bedworth Ratiomentioning
confidence: 99%